Supply chain technologies, interorganizational network and firm performance: A case study of Alibaba Group and Cainiao. Issue 3 (11th November 2019) - Falcone, Ellie; Kent, John; Fugate, Brian
Abstract : Purpose: Supply chain management literature recognizes that interorganizational networks provide resources that convey critical benefits, such as capital, competitive advantage and efficient strategy implementation. The purpose of this paper is to leverage network theory and identify technological innovations as the antecedents for organizations to achieve stronger interorganizational networks. Specifically, this paper investigates how supply chain technologies of its logistics affiliate, Cainiao Network (CN), affect Alibaba Group's three fundamental network mechanisms reachability, richness and receptivity and how interorganizational networks subsequently drive Alibaba Group's performance. Design/methodology/approach: A case study approach was chosen as a methodology to develop an in-depth understanding of the proposed innovations-network-performance framework. Findings: Results indicate that innovative technologies positively lead to network reachability, richness and receptivity. Stronger interorganizational networks directly lead to higher performance. In addition, CN is identified as a unique innovative business model. Originality/value: The key contribution of this research is that it investigates Alibaba Group's performance from a network and innovation perspective. It identifies technological innovations as a key driver for stronger interorganizational networks. Furthermore, three network mechanisms are introduced and investigated as the antecedents of organizational performance. This research also provides a comprehensive description of Alibaba Group and CN.